Sinonasal adenocarcinoma: A 16‐year experience at a single institution. Issue 10 (29th January 2014) - Bhayani, Mihir K.; Yilmaz, Turker; Sweeney, Alex; Calzada, Gabriel; Roberts, Dianna B.; Levine, Nicholas B.; DeMonte, Franco; Hanna, Ehab Y.; Kupferman, Michael E.
Abstract Background Adenocarcinoma is a rare tumor of the sinonasal tract. The purpose of this study was to characterize a single institution's experience with this malignancy. Methods Retrospective review was performed of patients with adenocarcinoma of the sinonasal tract from 1993 to 2009. Demographic data, disease presentation, treatment, and survival rates were collected and evaluated. Results We identified 66 patients with sinonasal adenocarcinoma; 48 were men and 18 women. Average age at time of diagnosis was 57.1 years (range, 20–88 years), and median follow‐up was 55.3 months (range, 1–238 months). The ethmoid sinus (38%) and nasal cavity (36%) were the most common sites of origin. Nasal obstruction (36%), epistaxis (30%), and nasal discharge (21%) were the most common presenting symptoms. Fifty‐one percent of patients presented with T1 or T2 tumors. Surgery was the primary form of treatment in 81% of patients. Twenty‐six percent of surgical patients underwent an endoscopic tumor resection. Adjuvant radiation was utilized in 50% of patients and chemotherapy in 10%. Recurrence was seen in 24 patients (37%): 29% recurred locally and 7.6% recurred distantly. The overall 5‐year survival was 65.9%. Survival was decreased significantly in patients with T4 tumors (p < .05), high‐grade histology (p < .05), and sphenoid sinus involvement (p < .05). Survival was not affected by surgical approach between endoscopic and open approaches (p = .76). Conclusion Sinonasal adenocarcinomas are commonly identified in the sinonasal cavity and are associated with a relatively favorable prognosis, despite a substantial local failure rate of 30%. Advanced‐stage tumors, sphenoid sinus and skull base invasion, and high‐grade histology portend poor prognosis. In our experience, endoscopic resection was not associated with adverse outcomes and suggests that this minimally invasive approach can provide acceptable oncologic outcomes in selected patients. © 2014 Wiley Periodicals, Inc. Head Neck, 36: 1490–1496, 2014